Citizen Science im Kaiserreich. Die Systemstelle „Wertlose Einsendungen aus der Bevölkerung" im Archiv der Berlin‐Brandenburgischen Akademie der Wissenschaften. Issue 4 (7th December 2018) - Krajewski, Markus
Abstract: Citizen Science in the Empire. The System Place "Wertlose Einsendungen aus der Bevölkerung" (Worthless Entries from the Population) in the Archives of the Berlin‐Brandenburg Academy of Sciences and Humanities . Between 1871 and 1946, the Berlin‐Brandenburg Academy of Sciences and Humanities maintained a special collection in its archives, which, under the simple name "Entries from the Population", kept correspondences, projects and proposals, for which a negative expert opinion was issued after thorough examination. The collection offers surprising insights into the pathologies and fantasies of mostly pseudo‐scientific researchers, inventors and discoverers, while at the same time revealing a glimpse of the topics of this epoch that moved the history of science. Using a selection of examples, this essay examines the economic cycles and archive practices of a largely forgotten source of what is now called Citizen Science.